2016
DOI: 10.1080/1612197x.2016.1216148
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal post-shot celebrations and their relationship with performance in elite handball

Abstract: Nonverbal behaviour has an important function in team sports, but research is limited.Adopting a psychological momentum (PM) framework, this study explores the relationship between a team's history of events, nonverbal post-shot celebrations in the form of gestures and touch shown by the shooter after scoring, and subsequent team performance during handball matches. A naturalistic design with systematic observation was chosen for the present study. Based on an existing coding scheme, 616 post-shot periods from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although other studies that focused on overt verbalizations and gestures in tennis reported debilitative effects of negative and facilitative effects of positive outward emotional reactions (e.g., Zourbanos et al, 2015 ), our results are in line with studies that did not report an effect on performance (e.g., Van Raalte et al, 2000 ). The inconsistency of these findings demonstrates that predicting sports performance in general is a difficult task ( Nevill et al, 2008 ), which could be supported by considering additional situational and personal variables (e.g., Moesch et al, 2018 ). Since emotions can have a stronger effect on observers when they are identifiable from the outside, the study of outward emotional reactions seems particularly suitable for understanding the interpersonal consequences of emotions, an area that has received scant attention in sport psychology ( Tamminen and Bennett, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies that focused on overt verbalizations and gestures in tennis reported debilitative effects of negative and facilitative effects of positive outward emotional reactions (e.g., Zourbanos et al, 2015 ), our results are in line with studies that did not report an effect on performance (e.g., Van Raalte et al, 2000 ). The inconsistency of these findings demonstrates that predicting sports performance in general is a difficult task ( Nevill et al, 2008 ), which could be supported by considering additional situational and personal variables (e.g., Moesch et al, 2018 ). Since emotions can have a stronger effect on observers when they are identifiable from the outside, the study of outward emotional reactions seems particularly suitable for understanding the interpersonal consequences of emotions, an area that has received scant attention in sport psychology ( Tamminen and Bennett, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have emphasized that the integration of different body channels provides better recognition rates than the use of a single channel ( Aviezer et al, 2012a , b ). One method to assess this component would be direct observation, which has already been successfully implemented in some sports, such as handball (cf., Moesch et al, 2015 , 2018 ).…”
Section: The Component Model Of Emotions In Sportsmentioning
confidence: 99%
“…While positive emotional expressions after scoring in a football penalty shootout were positively associated with winning the shootout (Moll et al, 2010), no effect of emotional expressions on the outcome of the subsequent point in table tennis has been observed (Fritsch et al, 2020). Moreover, in handball, it was shown that the expression of positive emotions after scoring a goal might enhance sports performance when the team is currently playing well, but that it can have a negative effect on sports performance when the team is currently playing poorly (Moesch et al, 2018). These findings indicate the potential of observational tools focusing on emotional expressions to contribute to a better understanding of the role of emotions in sports.…”
Section: Introductionmentioning
confidence: 99%
“…From an applied perspective, considering the effects emotional expressions can have on sports performance (e.g., Moll et al, 2010;Moesch et al, 2018), insights into the relation between emotional experiences and emotional expressions may help athletes regulate their emotions more effectively (Jekauc et al, 2021). Particularly the interplay between push and pull effects seems to have implications for the relation between emotional experiences and emotional expressions in sport.…”
Section: Introductionmentioning
confidence: 99%